ANALISIS QUALITY OF SERVICE VIDEO STREAMING YOUTUBE DAN RMA WLAN DI POLITEKNIK NEGERI SRIWIJAYA - Suroso Suroso; Ciksadan Ciksadan; Sholihatun Sholihatun (TESLA: Jurnal Teknik Elektro, 2020)
Sriwijaya State Polytechnic is an educational institution that provides wireless hotspots in every lecture building. With the increasing need for internet, especially on Youtube streaming, it is necessary to have an analysis in each lecture building to find out QoS (Quality of Service) and RMA (Reliability, Maintainability, and Availability) on the Wireless LAN network at Sriwijaya State Polytechnic. This study uses the Action Research method. For QoS measurement using wireshark software and Axence netTools by logging in through the hotspot for each department at the Sriwijaya State Polytechnic, to find out the performance of a network using PRTG (Paessler Router Traffic Grapher) software using the ping IP Address sensor will display the availability monitoring results. The results of the largest measurement of maximum bandwidth are 21,639,256 bit / s in the Business Administration Department, for the highest delay and jitter values are 36 ms and 0.050 ms in the KPA building (Administrative Head Office). The result of the largest packet loss is 0.093% in the Department of Electrical Engineering, for the largest throughput is 0.918 Mbit / s at 1080HD video quality in the Accounting Department. Monitoring RMA aims to determine the performance of an internet network with an Availability result of 99%, this is categorized in good condition. It can be concluded that the QoS measurement results based on the TIPHON version are categorized as very good and the RMA monitoring results have good network performance results as well.Keyword: Streaming Youtube, Parameter QoS, wireshark, RMA ABSTRAKPoliteknik Negeri Sriwijaya merupakan salah satu instansi pendidikan yang menyediakan wireless hotspot di setiap gedung kuliah. Dengan adanya kebutuhan internet yang semakin meningkat khususnya pada streaming Youtube  maka perlu adanya analisis disetiap gedung kuliah untuk mengetahui QoS (Quality of Servie) dan RMA (Reliability, Maintainability, and Availability) pada jaringan Wireless LAN di Politeknik Negeri Sriwijaya . Penelitian ini menggunakan  metode Action Research. Untuk pengukuran QoS menggunakan software wireshark dan Axence netTools dengan cara login melalui hotspot untuk masing-masing jurusan di Politeknik Negeri Sriwijaya sedangkan untuk mengetahui kinerja dari sebuah jaringan menggunakan software PRTG (Paessler Router Traffic Grapher) dengan menggunakan sensor ping IP Address akan menampilkan hasil monitoring availability. Hasil pengukuran terbesar bandwidth maksimal yaitu 21,639,256 bit/s di Jurusan Adminstrasi Bisnis, untuk  nilai delay  dan jitter tertinggi yaitu 36 ms dan 0,050 ms di gedung KPA (Kantor Pusat Administrasi). Hasil packet loss terbesar yaitu 0,093% pada Jurusan Teknik Elektro, untuk troughput  terbesar yaitu 1,681 Mbit/s pada kualitas video 1080HD pada Jurusan Akuntansi. Monitoring RMA bertujuan untuk mengetahui kinerja dari suatu jaringan internet dengan hasil Availability sebesar 99% hal ini dikategorikan dalam kondisi yang baik. Dapat disimpulkan  hasil  pengukuran  QoS berdasarkan versi TIPHON hasilnya dikategorikan sangat bagus dan untuk hasil monitoring RMA memiliki hasil kinerja jaringan  yang baik juga.Kata Kunci: Streaming Youtube, Parameter QoS, wireshark, RMA